Coffee consumption and alertness: a study among office workers in Jakarta - Herqutanto,; Rosemiarti, Tria; Dewi, Dian Kusuma; Soemarko, Dewi Sumaryani; Syam, Ari Fahrial (Frontiers in Nutrition, 2024)
Background: Coffee consumption is popular among office workers. it plays an important role in improving alertness due to its caffeine substances. Alertness is crucial for white-collar workers to support productivity and one of the parameters is alertness reaction time. The change of reaction time would be categorized into shorter and longer compared to the first measurement, before coffee consumption. The longer reaction indicated a decline of alertness. The objective of this study is to observe the relationship between coffee consumption and alertness improvement. Material and Methods: This is a cross-sectional study, comparing coffee drinkers and non-coffee drinkers. All participants underwent similar assessments on alertness using Lakassidaya tool and a 7-day fluid diary to record coffee consumption and caffeine intake. Alertness was measured in the morning (baseline) and 30 minutes after coffee consumption (end line). The participants of the study were office workers of a company in Jakarta, Indonesia. Results: There were 121 participants who completed the study with 47.1% (n= 57) participants being coffee drinkers. There was no difference in the characteristics of the respondents. The coffee consumption among these workers was 247 (157 -391) mL/day with caffeine intake was 72 (36 -121) mg/day which was lower than the mini mum amount to trigger positive alertness reaction. There was no significant association between coffee consumption and alertness (OR = 1.538 (0.288 -1.467); p-value = 0.403) as well as the change in reaction time between coffee drinkers and non-coffee drinkers (17.3 (1.4 -32.2) ms vs. 13.0 (-3.9 -26.0) ms; p-value = 0.111). However, there was a trend in the improvement of alertness among coffee drinkers as indicated by shorter reaction time in baseline (180 (160.2-195.2) ms compared to post-consumption (155 (146.6 -170.2) ms. Conclusions: There was no significant association between coffee consumption and alertness improvement between coffee drinkers and non-coffee drinkers among office workers in Jakarta, Indonesia.